1, 10-seco guaianolide-type sesquiterpenoids from Chrysanthemum indicum. Issue 9 (2nd September 2021) - Xue, Gui-Min; Xue, Jin-Feng; Zhao, Chen-Guang; Zhao, Zhen-Zhu; Zhi, Yan-Le; Du, Kun; Li, Han-Wei; Sun, Yan-Jun; Feng, Wei-Sheng
ABSTACT: A chemical investigation of the whole plant of traditional Chinese medicine, Chrysanthemum indicum L., led to the discovery of six guaianolide-type sesquiterpenoids 1–6 with a 1, 10-splited skeleton. The structure of the new compound 1 was established by extensive analysis of UV, IR, MS, NMR and ECD data. Compounds 3–6 are mutually stereoisomers with four chiral centers and their absolute configurations were determined by comparison of ECD spectra. The anti-inflammatory effects of these isolates on lipopolysaccharide (LPS)-induced nitric oxide (NO) were investigated in RAW 264.7 cells. Results showed that most of the compounds displayed NO production inhibitory activities with IC50 values ranged from 3.54 to 8.17  μ M. Graphical abstract: UF0001